Integrative Analysis of lncRNA and mRNA and Profiles in Postoperative Delirium Patients - Song, Yuxiang; Wang, Xiaoyan; Hou, Aisheng; Li, Hao; Lou, Jingsheng; Liu, Yanhong; Cao, Jiangbei; Mi, Weidong (Frontiers in Aging Neuroscience, 2021)
Delirium is a common serious complication that often occurs after major surgery. The goals of this study were to explore the expression profiles and functional networks of long non-coding RNAs (lncRNAs) and mRNAs in patients of postoperative delirium (POD). Microarray analysis was performed on the peripheral blood samples to identify differentially expressed (DE) lncRNAs and mRNAs in 4 POD patients and 4 non-POD volunteers. DE lncRNAs and mRNAs were validated by quantitative reverse transcription PCR (RT-qPCR). Bioinformatic analyses were performed to identify the critical biological functions and signaling pathways involved in POD. A total of 1195 DE lncRNAs and 735 DE mRNAs were identified between the POD and non-POD groups. Verified by the RT-qPCR, we identified 14 DE lncRNAs that may relate to the pathogenesis of POD. These 14 DE lncRNAs play important regulatory roles in “glutamate and 5-hydroxytryptamine,” “synaptotagmin 7,” “transient receptor potential channel,” “interleukin-2 production.” There was a regulatory relationship between lncRNA ENST00000530057 and synaptotagmin (Syt) 7 mRNA. The mRNA level of PCLO was up-regulated in POD group. This study showed abundant DE lncRNAs and mRNAs in POD that might help in deciphering the disease pathogenesis.